A Comprehensive Review on Various State-of-the-Art Techniques for Image Enhancement - S, Pallavi; M S, Sannidhan; Bhandary, Abhir (International Journal of Engineering and Technology, 2018)
Image processing involves many pre-processing techniques. One such technique is image enhancement. This is the most difficult phase in processing because it should enhance an image to such a clear visual level that human eyes should discern it. It is proven that the enhanced images are able to provide the high rate accuracy, increased efficiency, robust results in case of criminal investigations, security applications etc. Here, the goal is to enhance a degraded image, noisy, foggy or low-resolution image to obtain the output image which appears better than the original. This survey paper provides a brief analysis of techniques and algorithms of image enhancement.Â Â